Analyzing Generation Z's Internal Freedom Through Self-Concept Formation on Instagram - Setiawan, Fristian; Astuti, R.A. Vita (Kalijaga Journal of Communication, 2025)
Generation Z forms its self-concept through Instagram. The process of forming this self-concept is related to the concept of internal freedom. This concept is used to observe the process by which Gen Z forms their self-concept on Instagram, specifically to determine whether this process is based on their own freedom or external intervention. The purpose of this study is to identify and offer new ways of understanding and applying Gen Z's internal freedom in their efforts to form their self-concept on Instagram. This study employs a qualitative approach, utilizing a phenomenological method and in-depth interviews with eight Gen Z informants who are active personal Instagram users. The study's results reveal five key findings. The first is that some Gen Zers understand that they are not free to form their self-concept on Instagram, yet feel free to do so; however, they are actually not free either, and have felt unfree, only to eventually realize their freedom in forming their self-concept. The fourth finding is that some Gen Zers feel constrained in forming their self-concept due to their own freedom, and the last finding is that some Gen Zers genuinely feel free in forming their self-concept on Instagram. Based on these results, Gen Z's understanding and application of their freedom in forming their self-concept on Instagram shows that Gen Z interprets every interaction they experience with others as a truth to be heeded, rather than rejected.